2011
DOI: 10.1209/0295-5075/95/36001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-dynamics simulation of lateral friction in contact-mode atomic force microscopy of alkane films: The role of molecular flexibility

Abstract: Molecular-dynamics simulations are used to investigate lateral friction in contactmode atomic force microscopy of tetracosane (n-C24H50) films. We find larger friction coefficients on the surface of monolayer and bilayer films in which the long axis of the molecules is parallel to the interface than on a surface of molecules with the long axis perpendicular to the surface, in agreement with experimental results. A major dissipation mechanism is the molecular flexibility as manifested in the torsional motion ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Salmeron , has likewise considered extensively the pathways of load dissipation in alkane films, considering how chain tilt and the formation of both terminal and internal gauche defects play a role in this process. Finally, Soza et al demonstrate the formation of defects in tetracosane mono- and bilayers on a graphitic substrate after simulated scanning of an asperity across their surfaces and observed that friction is reduced upon artificial stiffening of the molecular torsions . This latter point implies that a more rigid film will produce lower friction by reducing energy dissipation into the surface, which is observed for more well-ordered, rigid SAMs. ,,, Defect formation, the conformational change from a trans methylene unit to a gauche methylene unit, is expected to increase on surfaces with curvature owing to the fact that, as the chains extend away from the surface, they must fill a greater volume.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Salmeron , has likewise considered extensively the pathways of load dissipation in alkane films, considering how chain tilt and the formation of both terminal and internal gauche defects play a role in this process. Finally, Soza et al demonstrate the formation of defects in tetracosane mono- and bilayers on a graphitic substrate after simulated scanning of an asperity across their surfaces and observed that friction is reduced upon artificial stiffening of the molecular torsions . This latter point implies that a more rigid film will produce lower friction by reducing energy dissipation into the surface, which is observed for more well-ordered, rigid SAMs. ,,, Defect formation, the conformational change from a trans methylene unit to a gauche methylene unit, is expected to increase on surfaces with curvature owing to the fact that, as the chains extend away from the surface, they must fill a greater volume.…”
Section: Resultsmentioning
confidence: 99%
“…It is commonly observed that disorder within the films increases as packing density decreases, and as a result, friction increases. There are two means by which increased disorder may increase friction: chemical effects, whereby the more disordered film has higher surface energy, and what may be described as kinetic effects, whereby dissipation is more favored in the less rigid, more disordered film. , Here packing is considered on flat, amorphous silica, where no underlying crystalline structure guides the packing of the film, using the same, uniform coverage assumption that was used in functionalization of the particle surfaces. It is important to note that OTS films on flat surfaces display considerable heterogeneity, with high and low density regions readily apparent by AFM imaging .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations